Application of a simplified definition of diastolic function in severe sepsis and septic shock. Issue 1 (December 2016) - Lanspa, Michael; Gutsche, Andrea; Wilson, Emily; Olsen, Troy; Hirshberg, Eliotte; Knox, Daniel; Brown, Samuel; Grissom, Colin
Abstract Background Left ventricular diastolic dysfunction is common in patients with severe sepsis or septic shock, but the best approach to categorization is unknown. We assessed the association of common measures of diastolic function with clinical outcomes and tested the utility of a simplified definition of diastolic dysfunction against the American Society of Echocardiography (ASE) 2009 definition. Methods In this prospective observational study, patients with severe sepsis or septic shock underwent transthoracic echocardiography within 24 h of onset of sepsis (median 4.3 h). We measured echocardiographic parameters of diastolic function and used random forest analysis to assess their association with clinical outcomes (28-day mortality and ICU-free days to day 28) and thereby suggest a simplified definition. We then compared patients categorized by the ASE 2009 definition and our simplified definition. Results We studied 167 patients. The ASE 2009 definition categorized only 35 % of patients. Random forest analysis demonstrated that the left atrial volume index and deceleration time, central to the ASE 2009 definition, were not associated with clinical outcomes. Our simplified definition used only e′ and E/e′, omitting the other measurements. The simplified definition categorized 87 % of patients. Patients categorized by either ASE 2009 or our novel definition had similar clinical outcomes. In both definitions, worsened diastolic function was associated with increased prevalence of ischemic heart disease, diabetes, and hypertension. Conclusions A novel, simplified definition of diastolic dysfunction categorized more patients with sepsis than ASE 2009 definition. Patients categorized according to the simplified definition did not differ from patients categorized according to the ASE 2009 definition in respect to clinical outcome or comorbidities.